INEQUALITY AND INTERNATIONAL TRADE: THE ROLE OF SKILL-BIASED TECHNOLOGY AND SEARCH FRICTIONS. (6th January 2016) - Ritter, Moritz
Abstract : I embed a competitive search model of the labor market into a small open economy model with heterogeneous firms and workers. Search frictions generate equilibrium unemployment and income inequality between identical workers, in addition to income differences between skill groups. A quantitative evaluation of the U.S. trade experience suggests that the effect of the increase in goods trade since 1980 may have contributed to the increase in the college premium, but not to the increase in residual inequality.